PERAN OTORITAS JASA KEUANGAN DALAM PENEGAKAN HUKUM PRAKTIK PINJAMAN ONLINE ILEGAL DI JAWA BARAT - Fakhirah Putri Wijaya; Devi Maya Sofa (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
Digital technology has revolutionized financial services, yet it has also triggered a surge in illegal online lending. By 2025, West Java recorded the highest cases in Indonesia with loans totaling IDR 20.23 trillion. The high loan rate is not only due to low digital financial literacy but also to the numerous attempts by illegal lenders to commit fraud, such as misusing personal data, charging high interest rates, and intimidating collection methods. The purpose of this research was to examine the role of the Financial Services Authority (OJK) in enforcing the law on illegal online lending practices in West Java, using two approaches: prevention and enforcement. This research used qualitative methods, examining written sources, official reports, regulations, and relevant case studies. The results indicate that the OJK's preventive efforts, such as improving financial literacy and disseminating information to the public, as well as publishing data on legitimate lenders, have had a positive impact. Enforcement efforts through blocking applications, tracking digital crimes, and using financial analysis to trace fund flows have proven quite effective, although illegal lenders continue to adapt and exploit technological gaps. This study recommends strengthening interagency cooperation, optimizing surveillance technology, enhancing data protection, and expanding financial education. These steps are vital to creating a secure and sustainable digital financial environment. This holistic approach ensures protection for all levels of society against evolving digital financial crimes.